Economic and social efficiencies of selected area farmer organizations in Malaysia - Mat Esa, Anuar (2013)
To fulfill highly expectations of the government and to retain continuous supports from the members, farmer's organization is anticipated to be an efficient organization. In order to remain relevant, the organization needs to perform like other co-operative organizations where economic and social performance becomes crucially important. This implies the needs for adequate measures in both areas of interests and the evaluation is supposed to portray their overall performances. Hence, one way to measure the ability of an organization is through efficiency measurement. Therefore, this paper examines the technical efficiency (TE) of Area Farmers Organization (AFOs) and determinant factors of efficiency for five years period; from 2006 to 2010. The efficiency is measured through three different dimensions namely as economic dimension, social dimension and socio-economic dimension. For the purpose of the study, a two stage Data Envelopment Analysis (DEA) is used. In the first stage, DEA applied to measure the efficiency score of 56 AFOs. In the second stage, the efficiency score obtained and regressed by using Tobit model. Based on previous study, determinant factors such as assets, location, year of operation, types of business, manager's education, size of business and size of membership serve as independent variables. For complimentary, the Malmquist Productivity Index (MPI) is employed to measure productivity. The efficiency analysis in the study reveals most of the AFOs are plagued with inefficiency and experienced of productivity regression. The average technical efficiency scores recorded at 0.708, 0.672 and 0.790 under economic, social and socio-economic dimensions respectively. Meanwhile The Total Factor Productivity (TFP) score of less than one reflect the decline in productivity growth. The average TFP recorded as 0.981 under economic dimension, 0.975 under social dimension and 0.9T/ under socio-economic dimensions. From MPI result, AFOs need to improve 8.5% scale efficiency under economic whereas 11.85% and 11.45% technology change under social and socioeconomic respectively. As for determinant factors, the variables liked location, age of operation, size of business and membership are found to have a positive relationship with efficiency level.